Stroboscopic microscopy—direct imaging of structure development and phase separation during spin‐coating. Issue 1 (20th November 2013) - Toolan, Daniel T. W.; Hodgkinson, Richard; Howse, Jonathan R.
ABSTRACT Spin‐coated polymer blends possess a rich variety of accessible non‐equilibrium morphologies, formed through a process of phase separation and self‐assembly, the complexities of which remain incompletely understood. The technique of stroboscopic microscopy has now been developed to allow direct observations of microscopic and mesoscopic morphological development during spin‐coating and has afforded unequivocal information regarding morphological development. The technique so far has three modes of operation providing information on topographical, compositional, and crystal development. In this review, we look at the technique's development, its applications and comment on the future potential for this technique. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 17–25